2019
DOI: 10.1051/epjconf/201922405002
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Model of Electrical Discharge Machining and Algorithm of Extreme Control Through Acoustic Signal

Abstract: Electrical discharge machining (EDM) is one of the most accurate methods for machining conductive materials and has a number of important applications. In the EDM process the occurrence of electric charges between cathode and anode is accompanied by vibroacoustic signals, which can be used to develop highly efficient control and diagnostics systems. Experimental studies and modelling of the dynamic system of the EDM process carried out in this study show that parameters of acoustic signals can be used to estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The cerium Ce and nickel Ni react with zinc Zn of brass very actively with the formation of intermetallides. The reaction of nickel Ni and zinc Zn at temperatures above 1000 • C has an explosive character that can be observed as a series of sparks in the interelectrode gap during processing [26,44,53,155,156]. The reaction of cerium Ce and zinc Zn has a more violent character that is typical for cerium.…”
Section: Mediummentioning
confidence: 99%
“…The cerium Ce and nickel Ni react with zinc Zn of brass very actively with the formation of intermetallides. The reaction of nickel Ni and zinc Zn at temperatures above 1000 • C has an explosive character that can be observed as a series of sparks in the interelectrode gap during processing [26,44,53,155,156]. The reaction of cerium Ce and zinc Zn has a more violent character that is typical for cerium.…”
Section: Mediummentioning
confidence: 99%
“…The pulses that have passed through the dielectric fluid (process S2 (t)) have a dynamic effect on the elastic system consisting of the workpiece and fixture, which has its own dynamic properties characterized by the modulus of the transfer function H2 (f). The dynamic impacts on the workpiece occur mainly due to evaporation of the workpiece material [10] and phase transitions in the workpiece material due to heating. The accelerometer installed on the workpiece side perceives vibrations (process S3 (t)) resulting from impacts of discharge pulses that have reached the workpiece surface and performed work associated with the formation of erosion craters.…”
Section: Assessment Of Vibroacoustic Emissions During Wedmmentioning
confidence: 99%
“…Based on this consideration, the amplitude of high-frequency vibrations (A) is related to the material removal rate (MRR) by the expression. In [10], experiments showed that simultaneous measurements of the dimensions of the craters formed via electroerosion and VA signals allow obtaining a monotonic dependence between the amplitude (A) of the high-frequency vibration signals and the MRR, determined by the volume of the craters:…”
Section: Materials Removal Rate (Mrr) Of the Wedmmentioning
confidence: 99%
See 1 more Smart Citation